2019
DOI: 10.3389/fmicb.2019.02521
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Biotransformation of Green Tea Catechins Induced by Different Carbon and Nitrogen Sources in Aspergillus niger RAF106

Abstract: Biotransformation of green tea catechins mediated by microbes and/or enzymes could increase their bioavailability and improve their health benefits, but the regulatory mechanism remains unclear. Here, Aspergillus niger RAF106 isolated from Pu-erh tea was proved to be capable of degrading gradually ester-catechins into non-ester-catechins with higher bioavailability and gallic acid (GA) in aqueous solution only containing green tea catechins, and the products displayed similar radical-scavenging activity in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Research confirms the highest antioxidant activity of flavonoids at pH ranging from 4 to 6 [71]. In other studies, reactions such as oxidation and/or polymerization have been observed to pH above 6.0 [72,73]. The pH value above 4 and high temperatures (above 20 • C) affect structural stability, favoring chemical degradation of both EGCG and thiamine [74][75][76].…”
Section: Discussionmentioning
confidence: 54%
“…Research confirms the highest antioxidant activity of flavonoids at pH ranging from 4 to 6 [71]. In other studies, reactions such as oxidation and/or polymerization have been observed to pH above 6.0 [72,73]. The pH value above 4 and high temperatures (above 20 • C) affect structural stability, favoring chemical degradation of both EGCG and thiamine [74][75][76].…”
Section: Discussionmentioning
confidence: 54%
“…Decreases in gallates and increases in GA were previously observed in pu-erh tea fermentation, , but the cause of these changes was unclear. In a recent work, six carboxylic ester hydrolases containing tannase domains were identified in industrially fermented pu-erh tea leaves using metaproteomics analysis .…”
Section: Resultsmentioning
confidence: 89%
“…All tea catechins show antioxidant activity and bioavailability, especially when they are in epimer forms [ 29 ]. The stoichiometry for EGCG degradation by tannase is formation of EGC and gallic acid, whereas EC and gallic acid are two major products formed by the degradation of ECG [ 30 ]. In recent decades, only a yeast R. diobovatum Q95 has been reported to produce tannase, which is active toward epicatechins [ 11 ]; however, its relative activity to catalyze the hydrolyses of EGCG and ECG was lower than that of the tannases reported in this study.…”
Section: Discussionmentioning
confidence: 99%